A cena de agón na Alceste de Euripides - Santos, Fernando Brandao dos (Agón: Competencia y Cooperación. De la antigua Grecia a la Actualidad. Homenaje a Ana María González de Tobia)
In this study, I examine the agon scene in Euripides' Alcestis. The agon is placed in the 4th episode, when Alcestis' corpse has recieved all preparations for the funeral, and Admeto has already accomodated Heracles in the palace, without telling him, however, about the last occurrences. This episode is the biggest of the play with 360 verses, what could cause the prolongation of the action and consequently the decline of the emotional tonus. Nevertheless, Euripides has composed this episode with very diversified elements, that it could be divided in scenes, what confers certain agitily to the events succession that accelerates the end of the play. I took as basis the commentaries by A. M. Dale and by L P. E. Parker, and whenever necessary, I have also recurred to the James Diggle?s and D. J Conacher?s editions. Another important text for the present discussion of the agon in Alcestis is the book by Michael Lloyd, The Agon in Euripides